ANALISIS PENGARUH PENAMBAHAN ABU CANGKANG KELAPA SAWIT TERHADAP FLEXIBILITAS DAN DURABILITAS ASPAL MODIFIKASI AC-BC PG 76 - Rosyad, Farlin; Pratama, Deni (Ensiklopedia of Journal, 2024)
Palm oil is one of the largest commodities in Indonesia, especially in the province of South Sumatra and every year its area increases. This has an impact on the large amount of waste produced from the palm oil processing factory itself, the waste in question includes palm oil shells, leftovers from processing palm fruit in palm oil factories. The aim of this research is to find out the effect of adding palm shell ash on the flexibility and durability values of modified asphalt and what is the optimal mixture for AC-BC pavement after adding palm shell ash as an additive which is substituted with stone ash with a percentage variation of 0 %, 4%, 6%, and 8% on AC-BC pavement mixtures. From the results of the Marshall test, it was concluded that as the percentage of palm shell ash increased, the flexibility value increased, with the highest value obtained at a percentage of 8% of palm shell ash with a VMA value of 14.96% (residual Marshall) and VIM of 4.57%. . The durability value obtained for the percentage of 0% palm oil shell ash is 91.98%, the percentage for 4% palm oil shell ash is 92.69%, and for the percentage of 6% palm oil shell ash is 93.25% and for the percentage 8% palm shell ash is 93.29%. From the results of this research, it was found that the value of the influence of the palm oil shell ash mixture on the flexibility and durability values had a positive impact on PG76 modified asphalt, where every percentage of palm oil shell ash still met the standard development specifications.Keywords: At least 3 words and a maximum of 6 words, (first word; second word; third word)